Totalitarnyi roman - Sorokin, Vyacheslav (Russia : A.K.V. Studio and AMA Studio with participation of Goskino, 1998)
Melodrama featuring a love affair between a Moscow intellectual and a provincial girl. The main hero escapes from Moscow to a small town after becoming involved in the protests against the Soviet intervention in Czechoslovakia. There he starts a relationship with a woman who is an archetypal product of the Soviet system, firmly believing in the advantages of socialism and feeling sorry for the suffering inhabitants of the brutal capitalist world. Their relationship is quickly spotted and monitored by local KGB agents. Trying to turn the girl into an informant, they ultimately open her eyes to the problems which for a long time she preferred to interpret according to the party directives.
Duration: 01:57:00
Keywords: Fiction films